Radiofrequency Ablation of Crista Terminalis Focal Atrial Tachycardia Using End Inspiration to Prevent Phrenic Nerve Paralysis - Pedro J. Diaz Delgado, MD; Juan Carlos Batlle, MD; Evan Saenger, DO; Sergio Mellado, MD; Juan Rodriguez Lopez, MD; Hemal M. Nayak, MD; Allen S. Anderson, MD; Alejandro Velasco, MD (JACC: Case Reports)
Background: Phrenic nerve injury is a serious complication of radiofrequency catheter ablation (RFA), potentially leading to diaphragmatic paralysis. Case Summary: A 42-year-old woman was admitted for an electrophysiological study and RFA for symptomatic supraventricular tachycardia using minimal conscious sedation. During the electrophysiological study, atrial tachycardia was induced, showing early activation at the crista terminalis of the posterior right atrium. Persistent phrenic nerve capture with diaphragmatic stimulation was noted with pacing, which correlated with respiration and disappeared during inspiratory breath hold. A quadripolar catheter placed in the right subclavian vein was used to maintain phrenic nerve capture. RFA was successfully performed at the end of inspiration with careful monitoring of diaphragmatic stimulation facilitated by verbal commands. Postablation, atrial tachycardia was no longer inducible, and no complications occurred after the procedure or during outpatient follow-up. Discussion: Proximity of the phrenic nerve to right-sided atrial structures can complicate ablation for atrial tachycardia. This was managed by deep inspiration and displacement of right atrium away from the phrenic nerve, facilitating successful RFA. Take-Home Message: Performing ablation during end inspiration with phrenic nerve displacement was effective and safe.